Historietas de Villa-Lobos: análise e interpretação - Adriano Lopes Sobrinho (2017)
This paper is a study about Historietas by Heitor Villa-Lobos. A six-song collection for piano and voice composed in 1920 about poems by Ribeiro Couto, Ronald de Carvalho, Manuel Bandeira, and Albert Samain. The first part of this paper reports on the peculiarities and spectacles of Villa-Lobos' work, including a discussion about his composing phases and his participation in Semana de Arte Moderna. The main objective of this paper is to join a historical and musicological reflection to the musical interpretation of his work, yet to be explored by musicians. Through several analyses, it, is intended to identify a predominant style in the songs, to propose an interpretation that is coherent historically as well as the music-lyrics connection, and the possible sound intended by the composer. A stylistic analysis of the song has been made based on a musical parameters study (sound, harmony, melody and rhythm), in accordance with Jan LaRue's methodology. Also, in this research, it is shown the poets' biographical features, as well as considerations about their poems. At last, the interpretative suggestions point out a way to a possible execution for the challenging Historietas.